Unmet needs of women with GDM: a health needs assessment in Sandwell, West Midlands. (10th December 2019) - Plant, Nicola; Šumilo, Dana; Chapman, Rachel; Webber, Jonathan; Saravanan, Ponnusamy; Nirantharakumar, Krishnarajah
ABSTRACT: Background: Gestational diabetes mellitus (GDM) affects over 4% of pregnancies in England. We investigated GDM epidemiology within ethnically diverse population and the current offer of services to women with previous GDM to reduce their type 2 diabetes mellitus (T2DM) risk. Methods: (i) Analysis of routinely collected maternity data examining GDM incidence and risk factors; (ii) local authority self-assessment questionnaire on public health interventions targeting women with previous GDM and (iii) service development discussions regarding the current pathway and areas for improvement. Results: Of 9390 births between 2014 and 2018, 6.8% had a record of GDM. High body mass index (BMI), maternal age, and ethnicity (South Asian and some mixed ethnic backgrounds) were independent predictors of GDM. There were no public health commissioned services specifically targeting women with previous GDM. Weaknesses in transition from secondary to primary care and areas for improvement when screening for GDM were identified. Conclusions: GDM burden in this population was high. Awareness should be raised on the importance of regular glucose testing and lifestyle modification to delay or prevent progression to T2DM, particularly within high risk groups. The potential for health visitors to contribute to this should be explored. Commissioners should review evidence to develop a flexible lifestyle services model to meet the specific needs of these women.